The influence of social stress on time perception and psychophysiological reactivity. (31st January 2017) - van Hedger, Kathryne; Necka, Elizabeth A.; Barakzai, Anam K.; Norman, Greg J.
Abstract: Time perception is a fundamental component of everyday life. Although time can be measured using standard units, the relationship between an individual's experience of perceived time and a standard unit is highly sensitive to context. Stressful and threatening stimuli have been previously shown to produce time distortion effects, such that individuals perceive the stimuli as lasting for different amounts of time as compared to a standard unit. As a highly social species, humans are acutely sensitive to social stressors; however, time distortion effects have not been studied in the context of social stress. We collected psychophysiological (electrocardiogram and impedance cardiography) and time perception data before, during, and after a modified version of the Trier Social Stress Test for 42 participants. Based on prior theories and evidence from the time perception literature, we hypothesized that experiencing a stressful event would result in time distortion. This hypothesis was supported by the data, with individuals on average reproducing short and long duration negative and positive stimuli as lasting longer after experiencing social stress, t (41) = −3.55, p  = .001, and t (41) = −4.12, p  < .001 for negative stimuli, and t (41) = −2.43, p  = .02, and t (41) = −3.07, p  = .004 for positive stimuli. However, changes in time perception were largely unrelated to psychophysiological reactivity to social stress. These findings are in line with some other studies of time distortion, and provide evidence for the interoceptive salience model of time perception. Implications for mechanisms of time distortion are discussed.